Reflective practitioners: expectations vs facts - Witkowska, Magdalena (Glottodidactica, 2010)
Over the years of working at school teachers gain experience that is necessary for their professional development. The teaching experience may appear of little value if teachers do not reflect upon it. Reflection is the key to success in teaching. The article presents the results of a questionnaire conducted with foreign language teachers from Gorzów Wielkopolski, Poland schools who were asked about their reflection. Many teachers (95%) reported that they reflected on their teaching and even made notes (50%). The research outcomes provide interesting facts about teachers’ reflections.